PENGARUH KOMUNIKASI, IKLIM KERJA, INSENTIF DAN KECERDASAN EMOSIONAL TERHADAP SEMANGAT KERJA DENGA KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING KARYAWAN PT.VIEBIE SINAR PELITA UJUNG BATU ROKAN HULU, RIAU - Midun Damadi Tanjung; Marnis '; Ahmad Rifqi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the influence of Communications, Climate Work, Incentives And Emotional Intelligence Against Morale With Organizational Commitment As an intervening variable On Employee PT.Viebie Pelita Sinar Ujung Batu Rokan Hulu, Riau. In this study there were six variables: Communications (X1), Climate Work (X2), Incentives (X3), Emotional Intelligence (X4) Organizational Commitment (Y1), and Morale (Y2). Population of this research is all employees PT.Viebie Pelita Sinar Ujung Batu with a sample of 38 respondents were selected using census method. Collecting data in this study is done by giving questionnaires to the respondents. In terms of data analysis, this study using Path Analysis. The results showed that the Work Climate variables, Incentives and Emotional Intelligence direct effect on Morale, while variable Communication does not directly affect Morale and Organizational Commitment also affect morale. Then variables Organizational commitment mediate labor relations climate variables, Incentives and Emotional Intelligence on morale, while variable organizational commitment does not mediate therelationship variable Communication on Morale.Keywords: Communications, Climate Work, Incentives,EmotionalIntelligence,Organizational Commitment ,and Morale